"It's all about incentive": Social technology as a potential facilitator for self-determined physical activity participation for young people with physical disabilities. (17th November 2018) - Knibbe, Tara Joy; McPherson, Amy C.; Gladstone, Brenda; Biddiss, Elaine
ABSTRACT: Purpose : To investigate the perceived role of social technologies in promoting physical activity participation for young people with physical disabilities and to identify design considerations that should be addressed when creating social technologies to promote physical activity. Method : Interactive design workshops for young people with physical disabilities aged 12–18 ( n = 8) were held. Data were analyzed using interpretive thematic analysis. Results : Young people perceived significant benefit for social technologies to promote physical activity as they have the potential to overcome many barriers to physical activity participation. Design features recommended by the participants included (1) options for diverse interests and preferences, (2) provision of informational support, (3) support through equitable technology design, (4) incentive through competition and play, and (5) opportunities to develop community. Conclusions : Social technology has potential to provide tailored, equitable opportunities for social engagement and physical activity participation for young people with physical disabilities through needs- and preference-specific design.